MODUS OF SOCIAL INTEGRITY: PRACTICE OF CONSTRUCTING PRODUCTIVE CO-BEING - I. I. Brodetskaya (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. Analysis is focused on the study of theoretical and methodological preconditions of social integrity phenomenon research. Trends in the conceptual base of modern social theory are focused on the research of social phenomenon, the study of the conditions and mechanisms for the development of sociality. This suggests the need to find new interpretive schemes. The methodology of political philosophy in the analysis of sociality was limited. This theory has brought the phenomenon of co-existence to the aspect of political discourse. In this regard, the reference to the existence of human co-beingness, mechanisms and modus of its formation is a necessary methodological step. It allows you to draw a parallel between the phenomenon of social integrity and totality. Existential installation integrity, unity of individual and social order is invested in the social context as a human desire to know the surrounding reality. Cognition is installation on the penetration deep into the object, understanding its nature. Cognition opens up the prospect of being a harmonious personality. Existential knowledge focuses on the identity of the co-existence and serves only the prospect of overcoming the limitations of the totality. The potential of this phenomenon allows penetration of rigid rational scheme of classical political methodology, introducing the community as a spiritual practice, the experience of communitas. Thus, as the research methodology used social integrity existential approach, which actualizes the potential of the spiritual foundations of co-existence. This methodological step allows disclosing sociality at a deep level of analysis as a spiritual practice to others, modus being-cognition of the human reality. Originality of this work is to extend the of heuristic possibilities of social theory in the analysis of the social problems aspect with the purpose construction of integrated research methodology problems. Conclusions. Thus, the study of co-existence existence reveals the modus, the conditions and practices of the phenomenon formation in modern society. It promotes the formation of methodological basis of social integrity problem analysis that can interpret the sociality crisis which modern researchers speak about.